2006
DOI: 10.1530/rep.1.00750
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of glucose transporter GLUT8 during mouse spermatogenesis

Abstract: GLUT8 is a facilitative glucose transporter expressed at high levels in the testis. In this study, we analyzed the GLUT8 expression in mouse testis during spermatogenesis by RT-PCR, Western blot and immunohistochemistry methods. Our results show that GLUT8 expression is limited to spermatids and spermatozoa in the testis. Expression begins when round spermatids are formed at postnatal day 24. The expression persists throughout spermiogenesis, and it is also detected in spermatozoa, but it is absent in more imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
44
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 30 publications
10
44
1
Order By: Relevance
“…SLC2A8 is a recently cloned member of the class III facilitative transporters and is expressed in the blastocyst stage embryo, heart, skeletal muscle, brain, spleen, prostate, intestine, and testis (Carayannopoulos et al 2000, Doege et al 2000, Gomez et al 2006. Currently, we have confirmed that SLC2A8 is highly expressed in the Leydig cells as well as in the innermost cells of the seminiferous tubules in the mouse testis and localizes in the acrosome, midpiece, and principal piece of the mouse sperm (Kim & Moley 2007).…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…SLC2A8 is a recently cloned member of the class III facilitative transporters and is expressed in the blastocyst stage embryo, heart, skeletal muscle, brain, spleen, prostate, intestine, and testis (Carayannopoulos et al 2000, Doege et al 2000, Gomez et al 2006. Currently, we have confirmed that SLC2A8 is highly expressed in the Leydig cells as well as in the innermost cells of the seminiferous tubules in the mouse testis and localizes in the acrosome, midpiece, and principal piece of the mouse sperm (Kim & Moley 2007).…”
Section: Introductionsupporting
confidence: 53%
“…However, factors involved in the development of male infertility with insulin-dependent diabetes are poorly understood. SLC2A8 is highly expressed in the testis (Carayannopoulos et al 2000, Doege et al 2000, Gomez et al 2006, Kim & Moley 2007) and as such may play a major role in substrate delivery to develop sperm. These observations led us to focus on SLC2A expression in diabetic male mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLC2A4 is well known as the important insulin-sensitive transporter and is expressed in insulin-responsive tissues [6,7]. SLC2A8 is a recently cloned member of the class III facilitative transporters and is expressed in the heart, skeletal muscle, brain, spleen, prostate, intestine, and testis and in the developing embryo at blastocyst stage [8][9][10][11]. We have shown that SLC2A8 is an insulin-sensitive transporter in mouse blastocyst and testis [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…8,[22][23][24][25] Mammalian testes and spermatozoa are known to utilize various glucose transporters (GLUTs) [26][27][28][29] that serve to transport glucose and/or fructose for critical sperm cell metabolism and function. 27,28,30,31 We have recently shown that CSC induces oxidative stress, DNA damage, and seminiferous tubule cell apoptosis in mice, ultimately leading to altered sperm motility. We also examined the effect of CSC exposure on a spermatocyte cell line, which represents the premeiotic stage of spermatogenesis (eg, primary spermatocytes).…”
Section: Introductionmentioning
confidence: 99%